Is source elevation an auditory distance cue? A preliminary study. (October 2022) - Lombera, Esteban N.; Guevara, Manuel A.; Vergara, Ramiro O.
The aim of this work was to evaluate whether the angular elevation of a sound source could generate auditory cues which improve the auditory distance perception in a similar way to that previously reported by visual modality. For this purpose, we compared ADP curves obtained with sources located both at the listeners' ears and at ground level. Our hypothesis was that the participants can interpret the relation between elevation and distance of ground-level sources (which are linked geometrically) so we expected them to perceive their distances more accurately than those at ear level. However, the responses obtained with sources located at ground level were almost identical to those obtained at the height of the listeners' ears, showing that, under the conditions of our experiment, auditory elevation cues do not influence auditory distance perception.